Description of Dementia in The Elderly Status in The Work Area Health Center Ibrahim Adjie Bandung (Indonesian Contemporary Nursing Journal (ICON Journal), 2018)
Number of elderly in Indonesia in 2014 was reached 18.8 million lives and in 2025 would reached 36 million lives. Along with the increasing age, change of cognitive function on elderly was increased. Impaired cognitive function on elderly may caused alteration on personality and disrupting daily activity. If it took progressively, they can lead to dementia. By knowing dementia status on elderly in society it may be used as a database on developing program that related with elderly health in society. The aim of this research was to achieve description of dementia status on elderly in society. The method that used on this research was descriptive with quantitative approaches. Data collected by using Early Dementia Questionnaire (EDQ) on 98 elderlies took by used stratified random sampling technique at Puskesmas Ibrahim Adjie work area Bandung city. Univariat analysis has done to saw description of dementia status on elderly based on respondent characteristic. The result of this research obtained as many as 38 respondents with presentation 38.8% experienced early dementia and 60 respondents with 61.2% respondents belong to normal category